ANALISIS PARTISIPASI WANITA DALAM PELESTARIAN TENUN IKAT SUKU DAYAK DESA DI RUMAH BETANG ENSAID PANJANG SINTANG - Clara Octaviany; Yohanes Bahari; Amrazi Zakso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe title of this thesis is Analysis of Women's Participation in the Preservation of Dayak Village Bonds in the Betang Ensaid Panjang House of Sintang District. The general problem in this study is "how do women participate in the conservation of the Dayak Desa ikat weaving in the betel house of Ensaid Panjang Sintang District" with the following sub-problems: 1) women's participation in the preservation of the village Dayak tribal weaving in the Ensaid Panjang District betang house Sintang; 2) the young population does not participate in the conservation of the village Dayak tribal weaving in the Betang Ensaid Panjang home of Sintang Regency; 3) Dayak ikat weaving craft is only done by women who have basic education in the preservation of village dayak ikat weaving in the betel house of Ensaid Panjang, Sintang Regency; 4) the efforts made by the ikat weaving craftsmen and village apparatus in the conservation of the village dayak ikat weaving in the betel house of Ensaid Panjang, Sintang Regency. This research uses a qualitative research method with an ethnographic approach. Data collection tools use by observation guides, interview guides and documentation. The results showed: 1) only women can work on the Dayak Desa ikat weaving and may not be done by men; 2) teenage girls have not been moved to weave and are still busy with their personal affairs; 3) the demands of work and different educational backgrounds make it impossible for women in the betang house to all work on woven weaving; 4) there are training activities for ikat weaving craftsmen, cultural performances and cultural exhibitions that are always held by the Office of culture and tourism.Keywords: Women's Participation, Preservation, Dayak Ikat Weaving